Geological map of Jutulsessen (Dronning Maud Land) - Elvevold, Synnøve; Engvik, A K; Hansen, C; Jacobs, J; Meiklejohn, I; Myhre, P I; Rudolph, E (Norsk Polarinstitutt, 2021)
Keywords: Dronning Maud Land; geologi; kart

Forskrift om etablering, drift og bruk av jordstasjon for satellitt i Antarktis - Kommunaldepartementet (Lovdata, 2017)
Keywords: Dronning Maud Land; jus; kommunikasjon; teknologi

East Antarctica and supercontinent configuration: the Dronning Maud Land perspective - Jacobs, Joachim; Elburg, Marlina; Läufer, Andreas; Jokat, Wilfried (Japan Geoscience Union, 2015)
The geology of East Antarctica and its correlation in major supercontinents is highly speculative, since only a very small part of it is exposed. Therefore a better connection between geology and geophysics is needed in order to correlate exposed regions with ice-covered, geophysically-defined, blocks. In Dronning Maud Land (DML), two distinct late Mesoproterozoic/early Neoproterozoic tectono-metamorphic provinces appear, separated by the major, NE-trending Forster Magnetic Anomaly and South Orvin Shear Zone. To the west of this lineament, the Maud Belt has clear affinities with Grenville-age continent-continent mobile belts. East of the Forster Magnetic Anomaly, juvenile rocks with early Neoproterozoic age (Rayner-age) and an accretionary character crop out. The international GEA-II expedition (2012) targeted a white spot on the geological map immediately to the E of the Forster Magnetic Anomaly. This area allows the characterization and ground-truthing of a large and mostly ice-covered region, the SE DML Province that had previously been interpreted as an older cratonic block. However, new SHRIMP/SIMS zircon analyses and their geochemistry indicates that the exposed basement consists of a ca. 1000-900 Ma juvenile terrane that is very similar to rocks in Sor Rondane. It lacks significant metamorphic overprint at the end of crust formation, but it shows medium to high-grade overprinting between ca. 630-520 Ma, associated with significant felsic melt production, including A-type granitoid magmatism. Therefore, the aeromagnetically distinct SE DML province does neither represent the foreland of a Late Neoproterozoic/EarlyPaleozoic mobile belt, nor a craton, as has previously been speculated. It more likely represents the more juvenile, westward continuation of Rayner-age crust (1000-900 Ma). To the west it abuts along the NE-trending Forster Magnetic Anomaly. The latter is interpreted as a suture, which separates typical Grenville-age crust of the Maud Belt (ca. 1200-1030 Ma) to the W from Rayner-age crust to the E. Therefore the larger eastern part of DML has clearly Indian affinities. Its juvenile character with a lack of metamorphic overprint at the end of crust formation points to an accretionary history along this part of the Indian segment of Rodinia, immediately following final Rodinia assembly.
Keywords: Dronning Maud Land; geofysikk; geologi

Forskrift om miljøvern og sikkerhet i Antarktis - miljødepartementet, Klima- og (Lovdata, 2013)
Keywords: Antarktis; Dronning Maud Land; forurensning; forvaltning; jus; miljøvern; naturvern

Geological map of Heimefrontfjella, Dronning Maud Land, Antarctica (Scale 1:250,000) - Jacobs, Joachim; Bauer, Wilfried; Kreutzer, Stefan; Patzelt, Gernot; Schmidt, Rainer; Schulze, Peter; Siegesmund, Siegfried; Spaeth, Gerhard; Thomas, Robert J; Weber, Klaus; Zarske, Gerd (PANGAEA, 2009)
The geological overview map was compiled from 15 geological maps (1 : 25,000) and is based on Jacobs et al. 1996. The topographic basemaps were adapted from unpublished 1:250,000 provisional topographic maps, Institut f. Angewandte Geodäsie, Frankfurt, 1983. Part of the contour lines are from Radarsat (Liu et al. 2001).
Keywords: Dronning Maud Land; geologi; kart; topografi

Radar Scattering Zones across Dronning Maud Land, East Antarctica - Müller, Karsten; Albert, Mary; Hamran, Svein Erik; Hagen, Jon Ove Methlie (International Glaciological Society, 2008)
Keywords: Dronning Maud Land; geovitenskap; glasiologi

Kvitkuven: Kronprinsesse Märtha Kyst (Norsk Polarinstitutt, 1997)
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Vestfjella Aust: Maudheimvidda (Norsk Polarinstitutt, 1997)
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Vestfjella Vest: Maudheimvidda (Norsk Polarinstitutt, 1997)
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Ahlmannryggen: Maudheimvidda (Norsk Polarinstitutt, 1996)
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Jutulstraumen: Maudheimvidda (Norsk Polarinstitutt, 1996)
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Nature environment map: Gjelsvikfjella and Western Mühlig-Hofmannfjella, Dronning Maud Land, Antarctica - Høgvard, K (Norsk Polarinstitutt, 1993)
Keywords: Dronning Maud Land; NARE 1984/85; NARE 1989/90; geografi; kartlegging

Digestibility of krill in crabeater seals and minke whales - Mårtensson, Per-Erik; Nordøy, Erling S; Blix, Arnoldus Schytte (1993)
Keywords: Dronning Maud Land; forskning; hvaler; krill; plankton; seler; zoologi

Satellite tracking of crabeater seals off Queen Maud Land in Antarctica - Nordøy, Erling S; Folkow, Lars P; Blix, Arnoldus Schytte (1993)
Keywords: Dronning Maud Land; satellitt; seler; telemetri; zoologi

Jutulsessen: Fimbulheimen (Norsk Polarinstitutt, 1992)
Keywords: Dronning Maud Land; Troll forskningsstasjon; geografi; kartlegging; satellite bilder

H.U. Sverdrupfjella: Fimbulheimen (Norsk Polarinstitutt, 1991)
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Jutulgryta: Fimbulheimen (Norsk Polarinstitutt, 1991)
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Mühlig-Hofmannfjella Nord: Fimbulheimen (Norsk Polarinstitutt, 1991)
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Mühlig-Hofmannfjella Sør: Fimbulheimen (Norsk Polarinstitutt, 1991)
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Heimfrontfjella Nord: Maudheimvidda (Norsk Polarinstitutt, 1988)
Keywords: Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Heimfrontfjella Sør: Maudheimvidda (Norsk Polarinstitutt, 1988)
Keywords: Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Development of chicks during extreme cold conditions: the Antarctic Petrel (Thalassoica antarctica) - Bech, Claus; Mehlum, Fridtjof; Haftorn, Svein (University of Ottawa Press, 1988)
Keywords: Dronning Maud Land; fugler; konferanse; kongress; ornitologi; zoologi

Flichnerfjella Nord: Fimbulheimen (Norsk Polarinstitutt, 1984)
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Norwegian Antarctic Research. Past and Present. - Orheim, Olav (University of Chile, 1977)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; NARE ekspedisjoner; Weddellhavet; geologi; glasiologi; havis; hvalfangst; kongress; marin biologi; marin geofysikk; marin geologi; meteorologi; oseanografi; symposium

Forposten: Fimbulheimen (Norsk Polarinstitutt, 1975)
Keywords: Den norske antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Svalbard - Jan Mayen - The Antarctic Possessions (Utenriksdepartementet, 1973)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Peter I. Øy; polarområdene

Annandagstoppane. Maudheimvidda (Norsk Polarinstitutt, 1972)
Keywords: Dronning Maud Land; geografi; kartlegging

Vestfjella Aust: Maudheimvidda (Norsk Polarinstitutt, 1972)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk Antarktisekspedisjon 1968-69; Norsk-britisk-svenske antarktisekspedisjon; flyfoto; geografi; kartlegging; luftfoto

Vestfjella Vest: Maudheimvidda (Norsk Polarinstitutt, 1972)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk Antarktisekspedisjon 1968-69; Norsk-britisk-svenske antarktisekspedisjon; flyfoto; geografi; kartlegging; luftfoto

Geology of western Queen Maud Land - Roots, Ernest Frederick (American Geographical Society, 1969)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geologi

Kronprinsesse Märtha Kyst - Maudheimvidda: Dronning Maud Land (Norsk Polarinstitutt, 1963)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geografi; kartlegging

Maudheimvidda Aust: Dronning Maud Land (Norsk Polarinstitutt, 1963)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geografi; kartlegging

Borgmassivet: Maudheimvidda (Norsk Polarinstitutt, 1962)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; flyfoto; geografi; kartlegging; luftfoto

Giæverryggen: Maudheimvidda (Norsk Polarinstitutt, 1962)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; flyfoto; geografi; kartlegging; luftfoto

Noteveksling mellom Norges regjering og Sør-Afrika-Sambandets regjering angående lån til Sør-Afrika-Sambandet av Norway Station beliggende i det norske biland Dronning Maud Land - Utenriksdepartementet (Statsrådsekretariatet, 1960)
Keywords: Dronning Maud Land; jus; politikk; stasjoner

Dronning Maud Land: Sør-Rondane - Luncke, Bernhard (Norsk Polarinstitutt, 1957)
Keywords: Antarktiske ekspedisjon 1946-47; Dronning Maud Land; Richard Evelyn Byrd; flyfoto; geografi; kartlegging; luftfoto

Sydishavet: Blad 2 - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1950)
Keywords: Bouvetøya; Dronning Maud Land; Sørishavet; geografi; kartlegging

Antarktiske fugler - Holgersen, Holger (Stavanger Museum. Naturhistorisk avdeling, 1949)
Keywords: Antarktis; Dronning Maud Land; fugler; ornitologi; zoologi

Lov om Bouvet-øya, Peter I's øy og Dronning Maud Land m.m. (bilandsloven) (Lovdata, 1930)
Keywords: Bouvetøya; Dronning Maud Land; Peter I. Øy; jus; lovgivning

Politiske forhold i Antarktis - Giæver, John Schjelderup ([s.n.])
Keywords: Bouvetøya; Dronning Maud Land; Norge; Peter I. Øy; ekspedisjoner; historie; internasjonal politikk; opdagelsesreiser; rett

Dronning Maud Land : proposed Norwegian names - [Marstrander, C.]
Keywords: Dronning Maud Land; geografi